Pediatric Challenges in Robot-Assisted Kidney Transplantation - Grammens, Julien; Schechter, Michal Yaela; Desender, Liesbeth; Claeys, Tom; Sinatti, Céline; VandeWalle, Johan; Vermassen, Frank; Raes, Ann; Vanpeteghem, Caroline; Prytula, Agnieszka; Silay, Mesrur Selçuk; Breda, Alberto; et al. (Frontiers in Surgery, 2021)
Kidney transplantation is universally recognized as the gold standard treatment in patients with End-stage Kidney Disease (ESKD). Robot-assisted kidney transplantation (RAKT) is gradually becoming preferred technique in adults, with potentially improved clinical outcomes compared with open kidney transplantation. To date, only very few RAKT procedures in children have been described. Kidney transplant recipient patients, being immunocompromised, might be at increased risk for perioperative surgical complications. Applying techniques of minimally invasive (MIS) surgery may contribute to the improvement of clinical outcomes for the pediatric transplant patients population and help mitigate the morbidity of KT. MIS has been consistently shown to produce improved clinical outcomes as compared to open surgery equivalents. Robot-Assisted Laparoscopic Surgery (RALS) in children poses additional challenges to both the surgical and anesthesiology team, due to specific characteristics such as a small abdominal cavity and a reduced circulating blood volume. Cost-effectiveness, esthetic and functional wound outcomes, minimal age and weight to undergo RALS and effect of RAKT on graft function are discussed. Although data on RAKT in children is scarce, it is a safe and feasible procedure and results in excellent graft function. It should only be performed by a RAKT team experienced in both RALS and transplantation surgery, fully supported by a pediatric nephrology and anesthesiology team. Further research is necessary to better determine the value of the robotic approach as compared to the laparoscopic and open approach. Cost-effectiveness will remain an important subject of debate and is in need of further evaluation as well.